DC-link capacitor voltage regulation with effort-reduction fuzzy logic control for three-level inverter-based shunt active power filter - Mailah, Nashiren Farzilah; Yap, Hoon; Mohd Radzi, Mohd Amran (Universiti Putra Malaysia Press, 2017)
Shunt active power filter (SAPF) is the most effective solution for current harmonics. In its controller, DC-link capacitor voltage regulation algorithm with either proportional-integral (PI) or fuzzy logic control (FLC) technique has played a significant role in maintaining a constant DC voltage across all the DC-link capacitors. However, PI technique performs poorly with high overshoot and significant time delay under dynamic state conditions, as its parameters are difficult to be tuned without requiring complete knowledge of the designated system. Although FLC technique has been developed to overcome limitations of PI technique, it is mostly developed with high complexity thereby increases computational burden of the designed controller. This paper presents a fuzzy-based DC-link capacitor voltage regulation algorithm with reduced computational efforts to enhance performance of three-phase three-level neutral-point diode clamped (NPC) inverter-based SAPF in overall DC-link voltage regulation. The proposed method is called effort-reduction FLC technique. The proposed algorithm is developed and evaluated in MATLAB-Simulink. Moreover, conventional algorithm with PI technique is tested for comparison purposes. Simulation results have confirmed improvement achieved by the proposed algorithm in comparison to the conventional algorithm.